Investigation of tabular methods in the system of residual classes - Koshman, S.; Krasnobayev, V.; Lunov, Y. (Національний технічний університет "Харківський політехнічний інститут", 2023)
The purpose of the report is to improve the productivity of computer tools for processing digital data presented in the system of residual classes. The report discusses the features of using tabular methods of information processing (TM) in SRC.
Keywords: information technology; processing speed; positional number system; tabular devices